2016
DOI: 10.31018/jans.v8i4.1069
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of steviol glycosides (stevioside and rebaudioside-A) with growth and development of Stevia rebaudiana Bertoni

Abstract: In the present investigation, the dynamics of steviol glycosides (stevioside and rebaudioside-A) of Stevia rebaudiana with their growth stages were studied. The study aimed to examine the best stage of harvesting (month of the year) the crop with respect to maximum accumulation of stevioside and rebaudioside-A content in different plant parts (leaves, green stem and woody stem). The results showed that the maximum stevioside content in leaves (8.55%) was found in June month (vegetative stage). Rebaudioside-A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Although the changes in the contents of stevioside and rebaudioside A through the different developmental stages were not as drastic as the other steviol glycosides, results obtained from the relative quantification indicated that their contents decrease when the plants entered the flowering stage. The findings from the present study are in agreement with previous reports which stated that the optimal harvesting time for stevia is at the vegetative stage or just before flowering (during the flower bud formation stage), due to the maximum accumulation of steviol glycosides, especially stevioside, rebaudioside A, and rebaudioside C 6,7,40,41 . Considering the fact that the levels of steviol glycosides and also flavonoids are high during the late vegetative stage, i.e., right before budding and during budding, it is reasonable to suggest that these stages are the optimal harvesting times for the local stevia cultivar.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Although the changes in the contents of stevioside and rebaudioside A through the different developmental stages were not as drastic as the other steviol glycosides, results obtained from the relative quantification indicated that their contents decrease when the plants entered the flowering stage. The findings from the present study are in agreement with previous reports which stated that the optimal harvesting time for stevia is at the vegetative stage or just before flowering (during the flower bud formation stage), due to the maximum accumulation of steviol glycosides, especially stevioside, rebaudioside A, and rebaudioside C 6,7,40,41 . Considering the fact that the levels of steviol glycosides and also flavonoids are high during the late vegetative stage, i.e., right before budding and during budding, it is reasonable to suggest that these stages are the optimal harvesting times for the local stevia cultivar.…”
Section: Resultssupporting
confidence: 92%
“…This suggested that the content of steviol glycosides was highest during the late vegetative and budding stages and decreased during the flowering stage. The decrease in the content of steviol glycosides could be attributed to the allocation of photoassimilates to the reproductive organs and the reduced transcription of the genes involved in steviol glycoside biosynthesis when the plants enter the flowering stage 5,6 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Powdered samples packed in thimbles were extracted with dichloromethane on a water bath using a Soxhlet apparatus for extracting the dichloromethane soluble fraction (Sasidharan et al, 2011). The residual samples in the thimbles (preextracted with dichloromethane) were then extracted with methanol to obtain the sweet compounds of stevioside and rebaudioside-A (Pol et al, 2007;Kumari et al, 2016). Methanol from the methanolic extract was removed by distillation and the sample was dried under vacuum.…”
Section: Extraction Of Stevioside and Rebaudioside-amentioning
confidence: 99%